2015
DOI: 10.1038/onc.2015.367
|View full text |Cite
|
Sign up to set email alerts
|

The role of APC/CCdh1 in replication stress and origin of genomic instability

Abstract: It has been proposed that the APC/C(Cdh1) functions as a tumor suppressor by maintaining genomic stability. However, the exact nature of genomic instability following loss of Cdh1 is unclear. Using biochemistry and live cell imaging of single cells we found that Cdh1 knockdown (kd) leads to strong nuclear stabilization of the substrates cyclin A and B and deregulated kinetics of DNA replication. Restoration of the Cdh1-dependent G2 DNA damage checkpoint did not result in G2 arrest but blocked cells in prometap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 50 publications
5
37
0
Order By: Relevance
“…We verified that this synchronization approach was successful by FACS analysis of propidium iodide/BrdU-stained cells ( Fig 6E). We found no discernible effect of CDH1 RNAi on cell cycle progression under these experimental conditions, although it was previously reported that G1 is shortened after CDH1 depletion after nocodazole release [34,35]. However, knockdown of CDH1 resulted in enhanced protein expression of E2F7 during PD0332991 treatment and after release, as well as the APC/C Cdh1 substrates CDC6 and aurora kinase A ( Fig 6F).…”
Section: A Feedback Loop Between E2f7/8 and Apc/c Cdh1mentioning
confidence: 47%
“…We verified that this synchronization approach was successful by FACS analysis of propidium iodide/BrdU-stained cells ( Fig 6E). We found no discernible effect of CDH1 RNAi on cell cycle progression under these experimental conditions, although it was previously reported that G1 is shortened after CDH1 depletion after nocodazole release [34,35]. However, knockdown of CDH1 resulted in enhanced protein expression of E2F7 during PD0332991 treatment and after release, as well as the APC/C Cdh1 substrates CDC6 and aurora kinase A ( Fig 6F).…”
Section: A Feedback Loop Between E2f7/8 and Apc/c Cdh1mentioning
confidence: 47%
“…Accordingly, Cdh1 -deficient mouse embryonic fibroblasts (MEFs) show reduced proliferation and accumulate chromosomal aberrations 15 . CDH1 knockdown in human bone osteosarcoma U2OS cells causes accumulation of cyclin A and cyclin B, premature entry into S-phase with reduced loading of pre-replication complexes onto DNA and accumulation of DNA double strand breaks (DSBs) during mitosis owing to the presence of replication intermediates 16 .…”
Section: Ubiquitin Ligases In Genome Maintenancementioning
confidence: 99%
“…The combination of ATRA with anthracycline-chemotherapy is standard of care in high risk APL. Our previous results demonstrated that depletion of Cdh1 prolongs S phase, promotes replication stress and genomic instability and acts synergistically on doxorubicin-induced cell cycle arrest in G2/M [25]. These observations provide an excellent explanation why the combination of ATRA und anthracyclines is highly efficient in (Cdh1 low) APL.…”
Section: Discussionmentioning
confidence: 78%
“…However, little is known about the role of Cdh1 in the hematopoietic system. In order to study the role of APC/C Cdh1 in AML, we analyzed the protein expression patterns of Cdh1 in primary human AML blasts and the role of Cdh1 knockdown (kd) on induced differentiation in two cell lines derived from different AML subtypes using our previously validated highly efficient short hairpin (sh)RNA against Cdh1 [4, 25]. Cdh1 expression was decreased in the vast majority of primary AML samples.…”
Section: Introductionmentioning
confidence: 99%